Rheological Study of Oil-Sand-Water Mixtures - Ismayilova, F.B.; Ismayilov, G.G.; Zeynalova, G.A. (Herald of Azerbaijan Engineering Academy, 2025)
Oil-gas practice shows that starting from wells up to delivery to a treatment station in industrial pipelines in most cases the transport of multicomponent and multiphase systems (oilwater-sand and other solids) is realized. The abnormal flow properties of these systems under field conditions during their collection, treatment, and transportation, as a rule causes certain problems and result in additional power consumption. So, the investigations of the formation reasons of such systems and their geophysical and hydraulic features are becoming actual. In this paper is given the results of study on the basis of roto viscometric studies of various oils of the "Muradkhanly" field on "Reotest-2", the influence of the content of various fractional compositions of sand on the rheological characteristics of water-oil systems. In particular, it was found that the effect of a bulk element on the viscosity properties of these systems is nonmonotonic and strongly depends on the water content in heterogeneous mixtures.